2005
DOI: 10.1029/2004gl021802
|View full text |Cite
|
Sign up to set email alerts
|

Observed electric fields associated with lightning initiation

Abstract: [1] In situ electric field (E) measurements and inferred lightning initiation locations of three cloud-to-ground flashes are used to identify a thunderstorm region in which the preflash E exceeded the threshold for runaway breakdown. The maximum measured E in the region was 186 kV m À1 at 5.77 km altitude, which for runaway electrons is equivalent to 370 kV m À1 at sea level; this E value is $130% of the estimated threshold for an avalanche of runaway electrons. In addition, the volume where E exceeded the run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 15 publications
8
107
1
2
Order By: Relevance
“…During thunderstorms, the maximum strength of electric fields has been found in the range of 850−1300 V/cm [1], or even up to 2000 V/cm [2,3]. In such strong fields, by accelerating or decelerating the charged particles in extensive air showers, the intensity of secondary cosmic rays could be influenced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During thunderstorms, the maximum strength of electric fields has been found in the range of 850−1300 V/cm [1], or even up to 2000 V/cm [2,3]. In such strong fields, by accelerating or decelerating the charged particles in extensive air showers, the intensity of secondary cosmic rays could be influenced.…”
Section: Introductionmentioning
confidence: 99%
“…They developed the theory of runaway breakdown (RB), now mostly referred to as relativistic runaway electron avalanche (RREA) [6]. Marshall et al [3,7], Dwyer [8] and Symbalisty et al [9] studied the strength of threshold field necessary for an avalanche to occur, which is dependent on the altitude. They found that the value was about 2800 V/cm at sea level.…”
Section: Introductionmentioning
confidence: 99%
“…During a lightning stroke, fields with strength close to the runaway threshold were recorded inside thunderclouds [Marshall et al, 1995a[Marshall et al, , 1995b[Marshall et al, , 2005. The enhancements of penetrating radiation [Parks et al, 1981;McCarthy and Parks, 1985;Eack et al, 1996aEack et al, , 1996bEack et al, , 2000Torii et al, 2009;Tsuchiya et al, 2007Tsuchiya et al, , 2009 whose source was in thunderclouds [Babich et al, 2010], were recorded during thunderstorm activity.…”
Section: Discussionmentioning
confidence: 99%
“…The measured magnitudes of the field strength in thunderclouds, for example [Marshall et al, 1995a[Marshall et al, , 1995b[Marshall et al, , 2005, correspond to the d of $3; therefore our simulations are carried out around this magnitude. Note, however, the chosen geometries of charge distribution both for the case of low-energy space radiation and CRS with profile L are dipole-like geometries widely used to model thundercloud field.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation